2019
DOI: 10.3991/ijet.v14i22.11761
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Opinions of Special Education Teachers Regarding the Use of Assistive Technologies for Overcoming Reading Difficulties

Abstract: Reading is one of the basic skills that the students’ need to achieve, however, it is also one of the important competencies that is essential for reaching knowledge. Reading difficulty is a main problem that many teachers are coming across in their classrooms. Students’ with reading disabilities not only hinder the teachers’ flow of the lesson it also hinders the development of the students life skills. With the revolution of the technology in the 21ST century, assistive technologies are seen to be applied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…According to Guo et al [56], in an article published in the journal Early Childhood Research Quarterly, in the quartile Q1 ranking, self-efficacy and effective communication skills are highlighted. Kart [59], in a paper published in the journal Education Sciences, in the quartile Q2 classification, highlights the skills of resilience and collaborative work. For Demirok et al [66], in an article published in the International Journal of Emerging Technologies in Learning (IJET), in the quartile Q2 ranking, effective communication skills are highlighted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Guo et al [56], in an article published in the journal Early Childhood Research Quarterly, in the quartile Q1 ranking, self-efficacy and effective communication skills are highlighted. Kart [59], in a paper published in the journal Education Sciences, in the quartile Q2 classification, highlights the skills of resilience and collaborative work. For Demirok et al [66], in an article published in the International Journal of Emerging Technologies in Learning (IJET), in the quartile Q2 ranking, effective communication skills are highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Kart and Kart [59], in a literature review study, among the skills investigated, highlight the relevance of collaborative work in promoting inclusion and they state that this is one of the factors that most influence student outcomes in an inclusive school and that negative impacts can be mitigated with policies and active collaboration between all stakeholders in the educational process. In this way, the soft skill that is evident in this study are collaborative work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a variance, as 11.4% of teachers said they did not have knowledge of high-tech AT, 29.2% of the participants had beginner-level knowledge, and 9.5% had expert knowledge, the results suggest that 50% of the teachers reported proficient knowledge regarding the use of high-tech AT for their students. Demirok et al (2019), in support of this finding, argued that AT produces positive results. The authors revealed that the generation opinions of teachers regarding AT utilization is promising and gradually evolving.…”
Section: Interpretation and Discussionmentioning
confidence: 61%
“…Based on a research paper by Sahin & Yorek [11] A well-designed adaptation should provide for safety and proactively prevent any possibility of hazardous situations, research has shown that it is possible for Visual Impaired students to learn and study scientific subjects as well as sighted students, provided that they are provided with a modified learning environment and are taught by teachers who are skilled in teaching science and math to Visually Impaired students. And also for educators to support their pupils learn crucial knowledge and capabilities, they need to be aware of available technology and special technology programs as stated in [12].…”
mentioning
confidence: 99%